2022
DOI: 10.3390/ijerph192315744
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the Neighborhood Environment, Physical Activity by Domain and Sitting Time in Brazilian Adults

Abstract: This study aimed to examine the association between the neighborhood environment and domain-specific physical activity and sitting time in Brazilian adults. This cross-sectional study included 1803 adults (53.7% women) from Brazil’s five regions (North, Northeast, Midwest, Southeast and South). The perception of the environment was evaluated via a questionnaire. We considered seven indicators of the neighborhood environment: land use mix-diversity, land use mix-access, street connectivity, walking/cycling faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…This observation is expected because as students' access increases, the active trip becomes more attractive and fun for students; thus, they are more likely to use the active travel mode. In studies, it was also shown that land use diversity is related to walkability [40,41]. In previous studies, only access to public transportation was measured, and it was found that the use of school buses by students decreases with increasing access to public transportation services [14,30].…”
Section: Discussionmentioning
confidence: 99%
“…This observation is expected because as students' access increases, the active trip becomes more attractive and fun for students; thus, they are more likely to use the active travel mode. In studies, it was also shown that land use diversity is related to walkability [40,41]. In previous studies, only access to public transportation was measured, and it was found that the use of school buses by students decreases with increasing access to public transportation services [14,30].…”
Section: Discussionmentioning
confidence: 99%